2017
DOI: 10.1038/s41598-017-16183-x
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine’s antidepressant effect is mediated by energy metabolism and antioxidant defense system

Abstract: Fewer than 50% of all patients with major depressive disorder (MDD) treated with currently available antidepressants (ADs) show full remission. Moreover, about one third of the patients suffering from MDD does not respond to conventional ADs and develop treatment-resistant depression (TRD). Ketamine, a non-competitive, voltage-dependent N-Methyl-D-aspartate receptor (NMDAR) antagonist, has been shown to have a rapid antidepressant effect, especially in patients suffering from TRD. Hippocampi of ketamine-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 68 publications
5
45
0
Order By: Relevance
“…Thus, the proteome of blood sEVs reflects in part molecular neurobiological processes activated by repetitive stress (Krishnan and Nestler, 2010; Carboni, 2015). Interestingly, the rapid-acting antidepressant effect of ketamine is mediated by the regulation of mitochondrial function in the hippocampus (Weckmann et al, 2017). Similarly, fluoxetine (but not imipramine) upregulates proteins, for example, Aldolase A and Park7, involved in mitochondrial biogenesis and oxidative defense in the hippocampus (Glombik et al, 2017), and these protective molecules were not detected after stress in EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the proteome of blood sEVs reflects in part molecular neurobiological processes activated by repetitive stress (Krishnan and Nestler, 2010; Carboni, 2015). Interestingly, the rapid-acting antidepressant effect of ketamine is mediated by the regulation of mitochondrial function in the hippocampus (Weckmann et al, 2017). Similarly, fluoxetine (but not imipramine) upregulates proteins, for example, Aldolase A and Park7, involved in mitochondrial biogenesis and oxidative defense in the hippocampus (Glombik et al, 2017), and these protective molecules were not detected after stress in EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that repeated sub-anesthetic ketamine has been shown to improve clinical outcomes for treatment-resistant depression (Zanos et al, 2016). Weckmann et al (2017) showed that Ketamine's antidepressant effect is mediated by energy metabolism and antioxidant defense system. Moreover, there is increasing evidence that ketamine injection after pilocarpine appears to be sufficient to reduce epileptic status (Dhote et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of MAPK also enhances H2O2 production, forming a positive amplification loop (Zhang et al, 2006). Ketamine's effects on oxidative stress are mediated, at least in part, by a mechanism dependent of MAPK signaling inhibition (Réus et al, 2016;Weckmann et al, 2017). Some treatments also improved neuronal injury after epilepsy by enhancing theNuclear factor E2-related factor 2/antioxidant response element (Nrf2/ARE) pathway to increase the antioxidative activity of the body (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine-induced neurodegeneration in neonatal rats followed by long-term cognitive deficits is thought to be mediated by ROS [41]. In contrast, ketamine is shown to be an antioxidant in mouse hippocampi [42], macrophages [43] and rat lungs [44]. The reason for such conflicting results may be attributed to the difference in ROS detection between in vitro and in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%